Detection of multiple circulating Leishmania species in Lutzomyia longipalpis in the city of Governador Valadares, southeastern Brazil. - Mariana Santos Cardoso; Gabrielle Ariadine Bento; Laila Viana de Almeida; Joseane Camilla de Castro; João Luís Reis-Cunha; Vanessa de Araújo Barbosa; Cristian Ferreira de Souza; Reginaldo Peçanha Brazil; Hugo Oswaldo Valdivia; Daniella Castanheira Bartholomeu (PLoS ONE, 2019)
Leishmaniasis encompasses a group of diverse clinical diseases caused by protozoan parasites of the Leishmania genus. This disease is a major public health problem in the New World affecting people exposed in endemic regions. The city of Governador Valadares (Minas Gerais/Brazil) is a re-emerging area for visceral leishmaniasis, with 191 human cases reported from 2008 to 2017 and a lethality rate of 14.7%. The transmission of the parasite occurs intensely in this region with up to 22% of domestic dogs with positive serology for the visceral form. Lu. longipalpis is one of the most abundant sand fly species in this area. Despite this scenario, so far there is no information regarding the circulating Leishmania species in the insect vector Lutzomyia longipalpis in this focus. We collected 616 female Lutzomyia longipalpis sand flies between January and September 2015 in the Vila Parque Ibituruna neighborhood (Governador Valadares/MG), which is located on a transitional area between the sylvatic and urban environments with residences built near a preserved area. After DNA extraction of individual sand flies, the natural Leishmania infections in Lu. longipalpis were detected by conventional PCR, using primers derived from kDNA sequences, specific for L. (Leishmania) or L. (Viannia) subgenus. The sensitivity of these PCR reactions was 0.1 pg of DNA for each Leishmania subgenus and the total infection rate of 16.2% (100 positive specimens). Species-specific PCR detected the presence of multiple Leishmania species in infected Lu. longipalpis specimens in Governador Valadares, including L. amazonensis (n = 3), L. infantum (n = 28), L. (Viannia) spp. (n = 20), coinfections with L. infantum and L. (Viannia) spp. (n = 5), and L. (Leishmania) spp (n = 44). Our results demonstrate that multiple Leishmania species circulate in Lu. longipalpis in Governador Valadares and reveal a potential increasing risk of transmission of the different circulating parasite species. This information reinforces the need for epidemiological and entomological surveillance in this endemic focus, and the development of effective control strategies against leishmaniasis.